Pengembangan Model Strategic Learning Enabler untuk Meningkatkan Produktivitas Generasi Z dalam Pendidikan Tinggi Digital - Chanita Christie; Christopher Cahyadi; Ferry Setiawan; Djuwansah Suhendro (Jurnal Riset Rumpun Agama dan Filsafat, 2026)
This study aims to develop a Strategic Learning Enabler model by reconfiguring the role of Information and Communication Technology (ICT) units to enhance Generation Z student productivity in digital higher education. The research is motivated by the gap between digital transformation demands and the predominantly technical-operational role of ICT units. Using a quantitative explanatory design, this study examines the causal relationships among ICT role reconfiguration, adaptive learning systems, and student productivity. Data were collected through questionnaires distributed to Generation Z students engaged in digital learning environments and analyzed using Structural Equation Modeling (SEM). The findings indicate that Generation Z students exhibit high responsiveness to structured tasks but lack continuity in learning activities due to weak self-regulated learning. The study also reveals that adaptive learning systems significantly mediate the relationship between ICT transformation and student productivity. The proposed model emphasizes digital governance, learning analytics, and micro-tasking structures as key components in building sustainable academic productivity. This research contributes both theoretically and practically by offering an institutional framework for digital learning transformation in higher education.